The Use of ChatGPT in Higher Education: Student and Lecturer’s Perspectives - Husnul Yakin; Yanti Wirza (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2024)
The research aims to compare the perspectives of students and lecturers on the use of Chat Generative Pre-trained Transformer (ChatGPT) in higher education. The research follows a comparative study design with a qualitative method. Purposive sampling is used to select participants, including an English lecturer from a university and the researcher, who is a postgraduate student. Data is collected through a semi-structured interview conducted via Zoom. The interview questions cover topics such as the impact of ChatGPT on education, the most involved subjects for ChatGPT, challenges in using ChatGPT, ethical considerations, and the positive and negative impacts of ChatGPT for students and lecturers. Thematic analysis is used to analyze the interview data and compare the perspectives of students and lecturers. The findings highlight the potential benefits of ChatGPT in enhancing the learning experience, providing access to information and resources, and assisting in various educational tasks. However, challenges such as finding specific materials and the need for appropriate keywords are identified. Ethical use is emphasized, and both positive and negative impacts are discussed, including the risk of overreliance and reduced human interaction.